Estructuración del sistema de mejoramiento continuo para las entidades del sector público caso Instituto Nacional de Evaluación Educativa (INEVAL) - Echeverría Tacinchano, Lizbeth Germania (2014)
In our country, the Ten-Year Education Plan 2006-2015 in its policy No. 6 Improving quality and equity of education and implementation of the national system of evaluation points as a line of action implementation and development of a national assessment system which will provide a participatory to take corrective decisions and restore the quality of education in Ecuador diagnosis.